Preparation method of electrostatic chuck
By performing precision processing and multiple sintering on the ceramic base of the electrostatic chuck, the problem of the inability to accurately measure the electrode layer data of the electrostatic chuck in the prior art is solved, and a higher service life and stability are achieved.
Patent Information
- Application Number
- CN202411404226.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-21
AI Technical Summary
The adsorption electrode of the existing electrostatic chuck is designed inside the ceramic, and it is impossible to determine the thickness, appearance, width and other data of the electrode layer through direct measurement, resulting in the inability to accurately measure the service life of the electrostatic chuck and the stability of the repeated batches.
The electrostatic chuck base is prepared by machine processing, and the ceramic slurry is obtained through ball milling and casting, and laminated and sintered. Then it is precision-processed by ceramic CNC and polishing machine, and finally the electrode is prepared by screen printing and multiple sintering. and combine it with the ceramic base.
Through precision processing and multiple sintering, the parallelism between the electrode layer and the ceramic surface can be better controlled, and the stability of the electrode layer morphology and size can be controlled, thereby improving the service life and stability of the electrostatic chuck.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrostatic chucks, and in particular to a method for preparing an electrostatic chuck. Background Art
[0002] Most of the current electrostatic chucks have adsorption electrodes designed inside the ceramic. After production, the inspection of the electrode part is limited to the detection of electrical properties and adsorption functional properties, and it is impossible to accurately measure the thickness, appearance, width and other data of the electrode layer.
[0003] The main drawback of the prior art is that it is impossible to determine whether there are internal defects in the electrode layer inside the ceramic by direct measurement, and to accurately measure, screen and control the service life of the electrostatic chuck and the stability of repeated batches. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing an electrostatic chuck to solve the problem raised in the background technology.
[0005] In order to solve the above technical problems, the technical solution of the present invention is:
[0006] A method for preparing an electrostatic chuck, wherein the electrostatic chuck is a Coulomb type electrostatic chuck, and the preparation method comprises:
[0007] S1: Prepare the electrostatic chuck base by machining;
[0008] S2: Alumina powder is used as a raw material, and a dispersant, a ceramic mixed powder, a high-purity alumina ball milling bead and a solvent are added in a ball milling process, wherein the solvent is any one of ethanol, toluene and xylene or a mixture of any two or more thereof, and the ball milling time is greater than or equal to 48 hours. After ball milling, a plasticizer and a binder are added and premixed, and the premixing time is greater than or equal to 24 hours. After mixing, the mixture is ball milled again for 24 to 48 hours to ensure sufficient mixing, and the mixed ceramic slurry is tape-casted and laminated to obtain two laminated bodies respectively;
[0009] S3: Debinding and sintering the two laminated bodies, the debinding temperature is 300-600°C, debinding is performed in a N2 atmosphere, the sintering temperature is 1400-1450°C, the sintering atmosphere is a mixture of H2 and N2, wherein H2 accounts for 40%-90%, and the high temperature stage sintering time is 6-11h, to obtain a first sintered body and a second sintered body;
[0010] S4: The first sintered body and the second sintered body are subjected to rounding, drilling, parallelism grinding, flatness grinding, and roughness polishing by means of a ceramic CNC, a polishing machine, and a grinding machine;
[0011] S5: Screen printing is performed on the processed first sintered body, the electrode material is tungsten paste, the metal paste for screen printing includes 5% to 25% of ceramic formula powder to adapt the shrinkage rate, and after printing, it is dried in an oven at a temperature of 40 to 70° C.;
[0012] S6: The printed first sintered body is subjected to a second sintering, the sintering temperature is 1350° C. to 1450° C., the sintering atmosphere is a mixture of H2 and N2, wherein H2 accounts for 40% to 90%, and the high temperature stage sintering time is 6 to 11 hours, to obtain a third sintered body;
[0013] S7: The third sintered body is combined with the second sintered body by glue with high thermal conductivity to obtain a combined body, and then the combined body is combined with the electrostatic chuck base by glue with matching thermal conductivity.
[0014] Preferably, if the electrostatic chuck is a JR type electrostatic chuck, the preparation method comprises:
[0015] S1: Prepare the electrostatic chuck base by machining;
[0016] S2: Alumina powder is used as a raw material, titanium dioxide material is added, and the amount of titanium dioxide added is 0.4% to 2.5%. A dispersant, a ceramic mixed powder, a high-purity alumina ball milling beads and a solvent are added in a first ball milling process, wherein the solvent is any one of ethanol, toluene, and xylene or any two or a mixture of the two. The ball milling time is greater than or equal to 48 hours. After ball milling, a plasticizer and a binder are added and premixed. The premixing time is greater than or equal to 24 hours. After mixing, ball milling is performed for another 24 to 48 hours to fully mix the contents. The obtained ceramic slurry is tape-casted and laminated to obtain a laminated body.
[0017] S3: debinding and sintering the laminated body, the debinding temperature is 300-600°C, debinding is performed under N2 atmosphere, the sintering temperature is 1400-1450°C, the sintering atmosphere is a mixture of H2 and N2, wherein H2 accounts for 40%-90%, and the high temperature stage sintering time is 6-11h, to obtain a fourth sintered body;
[0018] S4: performing secondary sintering on the fourth sintered body while being suspended by a fixture, raising the sintering temperature to 1580° C. to 1620° C., using a sintering atmosphere of H2 and N2 mixed gas, wherein the proportion of H2 is greater than or equal to 80%, and the high temperature stage sintering time is 10 to 12 hours, to obtain a fifth sintered body;
[0019] S5: The fifth sintered body is subjected to rounding, drilling, parallelism grinding, flatness grinding, and roughness polishing by means of a ceramic CNC, a polishing machine, and a grinder;
[0020] S6: Screen printing is performed on the processed fifth sintered body, the electrode material is tungsten slurry, 5% to 25% of ceramic formula powder is added to the metal slurry for screen printing to adapt the shrinkage rate, and after printing, it is dried in an oven at 40 to 70° C.;
[0021] S7: sintering the printed fifth sintered body three times, the sintering temperature is 1350° C. to 1450° C., the sintering atmosphere is a mixture of H2 and N2, wherein H2 accounts for 40% to 90%, and the high temperature stage sintering time is 6 to 11 hours, to obtain a sixth sintered body;
[0022] S8: combining the sixth sintered body and the electrostatic chuck base by using glue with matching thermal conductivity.
[0023] The above technical solution has the following beneficial effects:
[0024] By metallizing the processed ceramic substrate, the obtained electrostatic chuck can better control the parallelism between the electrode and the upper surface, and at the same time can obtain an electrode layer with more stable morphology and size through detection and screening, thereby improving the service life and stability of the electrostatic chuck. DETAILED DESCRIPTION
[0025] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0026] Example 1
[0027] A method for preparing an electrostatic chuck, wherein the electrostatic chuck is a Coulomb type electrostatic chuck, and the preparation method comprises the following steps:
[0028] S1: Prepare an electrostatic chuck base by machining, and the electrostatic chuck base may be a metal base;
[0029] S2: Alumina powder is used as a raw material, and a dispersant, a ceramic mixed powder, a high-purity alumina ball milling bead and a solvent are added during a ball milling process, wherein the solvent is any one of ethanol, toluene and xylene. In other embodiments of the present embodiment, the solvent is a mixture of any two or three of ethanol, toluene and xylene. The ball milling time is 48 hours, or more than 48 hours. After ball milling, a plasticizer and a binder are added and premixed. The premixing time is 24 hours, or more than 24 hours. After premixing, the mixture is ball milled again for 24 hours. In other embodiments of the present embodiment, the ball milling time after premixing is 48 hours to ensure sufficient mixing. The mixed ceramic slurry is tape-casted, and two laminated bodies are obtained by lamination.
[0030] S3: Debinding and sintering the above two laminated bodies, the debinding temperature is 300°C, in other embodiments of the present embodiment, the debinding temperature is 600°C, debinding is carried out in N2 atmosphere, the sintering temperature is 1400°C or 1450°C, in other embodiments of the present embodiment, the sintering temperature is 1425°C, the sintering atmosphere is a mixture of H2 and N2, wherein H2 accounts for 40% or 90%, and the rest of the atmosphere is N2, in other embodiments of the present embodiment, H2 accounts for 65%, and the rest of the atmosphere is N2, the high temperature stage sintering time is 6 or 11h, or 8.5h, to obtain a first sintered body and a second sintered body;
[0031] S4: The first sintered body and the second sintered body are cut into circles by a ceramic CNC, and the first sintered body and the second sintered body are subjected to parallelism grinding, flatness grinding, and roughness polishing by a polishing machine and a grinder to ensure the quality of the first sintered body and the second sintered body;
[0032] S5: Screen printing is performed on the processed first sintered body, the electrode material is tungsten slurry, and the metal slurry for screen printing includes 5% to 25% of ceramic formula powder to adapt the shrinkage rate, that is, alumina powder for preparing ceramics is added to the metal slurry for screen printing, and after printing, it is dried in an oven at a temperature of 40° C. or 70° C. In other implementations of this embodiment, after printing, it is dried in an oven at a temperature of 55° C. The specific temperature selection needs to be adjusted according to the organic additive;
[0033] S6: The printed first sintered body is sintered for the second time, and the sintering temperature is 1350°C or 1450°C. In other implementations of this embodiment, the sintering temperature is 1400°C. The specific sintering temperature is adjusted according to the ratio of the electrode slurry and the ceramic formula powder. The sintering atmosphere is a mixture of H2 and N2, wherein H2 accounts for 40% to 90%, preferably 55% to 75%, specifically, H2 accounts for 40% or 90%, or 55% or 75%, and the rest is N2. The high temperature stage sintering time is 6h or 11h, and a third sintered body is obtained after sintering;
[0034] S7: combining the third sintered body and the second sintered body by glue with high thermal conductivity to obtain a combined body, and then combining the combined body and the electrostatic chuck base by glue with matching thermal conductivity, such as silicone, to prepare the electrostatic chuck;
[0035] The main materials of the ceramic part of the electrostatic chuck include but are not limited to aluminum oxide, aluminum nitride, and silicon carbide. The additives include but are not limited to titanium dioxide, yttrium oxide, calcium oxide, silicon dioxide, magnesium oxide and other metal oxides. The sintered ceramic plate is surface ground and punched, and then metal electrodes are printed on the processed ceramic substrate. The electrode materials include but are not limited to tungsten, molybdenum, titanium, platinum, palladium, etc. After drying, secondary debinding sintering and metallization are carried out;
[0036] The present application uses the technology of electrode printing after sintering and secondary sintering metallization to make the metal electrode on the surface of the ceramic. Firstly, it can better ensure the parallelism between the electrode layer and the upper surface of the ceramic. Secondly, it can directly measure and observe the electrode layer of the processed ceramic plate. For the Coulomb type electrostatic chuck, a piece of ceramic of the same material can be attached under the ceramic plate on this basis, so that the dielectric layer can be ground thinner later.
[0037] By metallizing the processed ceramic substrate, the obtained electrostatic chuck can better control the parallelism between the electrode and the upper surface, and at the same time can obtain an electrode layer with more stable morphology and size through detection and screening, thereby improving the service life and stability of the electrostatic chuck.
[0038] Example 2
[0039] A method for preparing an electrostatic chuck, wherein the electrostatic chuck is a JR type electrostatic chuck, and the preparation method comprises the following steps:
[0040] S1: Prepare the electrostatic chuck base by machining;
[0041] S2: Alumina powder is used as a raw material, titanium dioxide material is added, and the amount of titanium dioxide added is 0.4% or 2.5%. In other embodiments of this embodiment, the amount of titanium dioxide added is 1.6%. A dispersant, a ceramic mixed powder, a high-purity alumina ball milling beads and a solvent are added in a ball milling process, wherein the solvent is any one of ethanol, toluene and xylene or any two or a mixture of the two. The ball milling time is 48 hours, or more than 48 hours. After ball milling, a plasticizer and a binder are added and premixed. The premixing time is 24 hours, or more than 24 hours. After mixing, ball milling is performed for 24 hours or 48 hours, or 36 hours. The contents are fully mixed, and the obtained ceramic slurry is tape-casted and laminated to obtain a laminated body.
[0042] S3: debinding and sintering the laminated body, the debinding temperature is 300°C or 600°C, or the debinding temperature is 45°C, the debinding is carried out in an N2 atmosphere, the sintering temperature is 1400°C or 1450°C, the sintering atmosphere is a mixture of H2 and N2, wherein the H2 accounts for 40% or 90%, and in other implementations of this embodiment, the H2 accounts for 65%, the high temperature stage sintering time is 6h or 11h, and the sintering time can also be 8h, to obtain a fourth sintered body;
[0043] S4: the fourth sintered body is subjected to secondary sintering in the case of being suspended by a fixture, the sintering temperature is increased to 1580°C or 1620°C, or 1600°C, the sintering atmosphere is a mixture of H2 and N2, the H2 ratio is 80%, or more than 80%, the high temperature stage sintering time is 10h or 12h, or the high temperature sintering is 11h, to obtain a fifth sintered body;
[0044] S5: The fifth sintered body is cut and punched by ceramic CNC, and the fifth sintered body is ground in parallel, flat and roughness by polishing machine and grinder to ensure the quality of electrostatic chuck ceramics;
[0045] S6: Screen printing is performed on the processed fifth sintered body, the electrode material is tungsten slurry, 5% or 25% of ceramic formula powder is added to the metal slurry for screen printing to adapt the shrinkage rate, and 15% of ceramic formula powder can also be added, that is, aluminum oxide powder and titanium dioxide material are added to the metal slurry to adapt the shrinkage rate, and after printing, it is dried in an oven at 40° C. or 70° C.;
[0046] S7: sintering the printed fifth sintered body three times, the sintering temperature is 1350° C. or 1450° C., the sintering temperature can also be 1400° C., the sintering atmosphere is a mixture of H2 and N2, wherein H2 accounts for 40% or 90%, and H2 accounts for 60%, and the high temperature stage sintering time is 6h or 11h, to obtain a sixth sintered body;
[0047] S8: The sixth sintered body is combined with the electrostatic chuck base by using glue with matching thermal conductivity, thereby completing the preparation of the electrostatic chuck.
[0048] The technical solution of the present application metalizes the processed ceramic substrate, and the resulting electrostatic chuck can better control the parallelism between the electrode and the upper surface. At the same time, an electrode layer with more stable morphology and size can be obtained through detection and screening, thereby improving the service life and stability of the electrostatic chuck.
[0049] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A method for preparing an electrostatic chuck, characterized in that: The electrostatic chuck is a Coulomb type electrostatic chuck, and the preparation method comprises: S1: Prepare the electrostatic chuck base by machining; S2: Alumina powder is used as a raw material, and a dispersant, a ceramic mixed powder, a high-purity alumina ball milling bead and a solvent are added in a ball milling process, wherein the solvent is any one of ethanol, toluene and xylene or a mixture of any two or more thereof, and the ball milling time is greater than or equal to 48 hours. After ball milling, a plasticizer and a binder are added and premixed, and the premixing time is greater than or equal to 24 hours. After mixing, the mixture is ball milled again for 24 to 48 hours to ensure sufficient mixing, and the mixed ceramic slurry is tape-casted and laminated to obtain two laminated bodies respectively; S3: Debinding and sintering the two laminated bodies, the debinding temperature is 300-600°C, debinding is performed in a N2 atmosphere, the sintering temperature is 1400-1450°C, the sintering atmosphere is a mixture of H2 and N2, wherein H2 accounts for 40%-90%, and the high temperature stage sintering time is 6-11h, to obtain a first sintered body and a second sintered body; S4: The first sintered body and the second sintered body are subjected to rounding, drilling, parallelism grinding, flatness grinding, and roughness polishing by means of a ceramic CNC, a polishing machine, and a grinding machine; S5: Screen printing is performed on the processed first sintered body, the electrode material is tungsten paste, the metal paste for screen printing includes 5% to 25% of ceramic formula powder to adapt the shrinkage rate, and after printing, it is dried in an oven at a temperature of 40 to 70° C.; S6: The printed first sintered body is subjected to a second sintering, the sintering temperature is 1350° C. to 1450° C., the sintering atmosphere is a mixture of H2 and N2, wherein H2 accounts for 40% to 90%, and the high temperature stage sintering time is 6 to 11 hours, to obtain a third sintered body; S7: The third sintered body is combined with the second sintered body by glue with high thermal conductivity to obtain a combined body, and then the combined body is combined with the electrostatic chuck base by glue with matching thermal conductivity.
2. The method for preparing an electrostatic chuck according to claim 1, characterized in that: If the electrostatic chuck is a JR type electrostatic chuck, the preparation method comprises: S1: Prepare the electrostatic chuck base by machining; S2: Alumina powder is used as a raw material, titanium dioxide material is added, and the amount of titanium dioxide added is 0.4% to 2.5%. A dispersant, a ceramic mixed powder, a high-purity alumina ball milling beads and a solvent are added in a first ball milling process, wherein the solvent is any one of ethanol, toluene, and xylene or any two or a mixture of the two. The ball milling time is greater than or equal to 48 hours. After ball milling, a plasticizer and a binder are added and premixed. The premixing time is greater than or equal to 24 hours. After mixing, ball milling is performed for another 24 to 48 hours to fully mix the contents. The obtained ceramic slurry is tape-casted and laminated to obtain a laminated body. S3: debinding and sintering the laminated body, the debinding temperature is 300-600°C, debinding is performed under N2 atmosphere, the sintering temperature is 1400-1450°C, the sintering atmosphere is a mixture of H2 and N2, wherein H2 accounts for 40%-90%, and the high temperature stage sintering time is 6-11h, to obtain a fourth sintered body; S4: performing secondary sintering on the fourth sintered body while being suspended by a fixture, raising the sintering temperature to 1580° C. to 1620° C., using a sintering atmosphere of a mixture of H2 and N2, wherein the proportion of H2 is greater than or equal to 80%, and the high temperature stage sintering time is 10 to 12 hours, thereby obtaining a fifth sintered body; S5: The fifth sintered body is subjected to rounding, drilling, parallelism grinding, flatness grinding, and roughness polishing by means of a ceramic CNC, a polishing machine, and a grinder; S6: Screen printing is performed on the processed fifth sintered body, the electrode material is tungsten slurry, 5% to 25% of ceramic formula powder is added to the metal slurry for screen printing to adapt the shrinkage rate, and after printing, it is dried in an oven at 40 to 70° C.; S7: sintering the printed fifth sintered body three times, the sintering temperature is 1350° C. to 1450° C., the sintering atmosphere is a mixture of H2 and N2, wherein H2 accounts for 40% to 90%, and the high temperature stage sintering time is 6 to 11 hours, to obtain a sixth sintered body; S8: combining the sixth sintered body and the electrostatic chuck base by using glue with matching thermal conductivity.
Citation Information
Cited By
Silicon carbide electrostatic chuck based on tape casting and preparation method thereof
CN121318460A